Cognitive and Social Functioning Deficits after Anti-N-Methyl-D-Aspartate Receptor Encephalitis: An Exploratory Case Series. (22nd August 2016) - McKeon, Gemma L.; Scott, James G.; Spooner, Donna M.; Ryan, Alexander E.; Blum, Stefan; Gillis, David; Langguth, Daman; Robinson, Gail A.
Abstract: Background: Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a recently described life-threatening autoimmune disorder associated with a characteristic multi-stage neuropsychiatric syndrome. Although it is known that the majority of patients experience neuropsychological disturbance post-treatment, some aspects of the cognitive profile remain unclear.Methods: This study sought to investigate patterns of cognitive functioning in a sample of anti-NMDAR encephalitis patients. Seven (6F:1M; mean age, 26.4 years; range, 16–37 years) treated patients completed a comprehensive set of neurocognitive and social functioning measures. Performance was analyzed using normative data (where available), and comparison with matched controls (10F:4M; mean age, 25.8 years; range, 16–38 years).Results: Individual cognitive profiles ranged from within normal limits to extensive dysfunction. Relative to controls, the patient group's performance was affected in the domains of verbal/ visual memory, working memory, attention, processing speed, executive functioning, and social cognition. The patient group also reported significantly higher levels of anxiety compared to controls.Conclusions: These results add to the accumulating evidence that neurocognitive deficits, consistent with the distribution and functions of the NMDAR system can persist during recovery from anti-NMDAR encephalitis. This is the first study to provide evidence of performance decrements on measures of social cognition, including some involving theory of mind. ( JINS, 2016, 22, 828–838)